A critical analysis of North American business leaders’ neocolonial discourse: global fears and local consequences - McKenna, Stephen (The International Society for Organization Development, 2011)
Using a postcolonial analytic frame and critique this article investigates the nature of the discourse used by 24 North American business leaders to describe, understand and make sense of the economic development of China and India and contemporary international encounters. In particular the article investigates how business leaders discursively characterize this ‘threat’, how they (re)present China and India and, how they discursively construct the requirements of a response to this ‘threat’. An analysis of the interviews indicates the persistence of the discourse of (neo)colonialism (Orientalism) in the construction of the Other within the context of a view of China and India as developing and progressing towards a North American ideal. Despite this, North American business leaders also show ambivalence and uncertainty towards China and India. On the one hand they laud their success while damning them for their apparently exploitative social, economic and workplace systems and practices. Moreover, while they promote a Western development discourse concerning China and India, North American business leaders recognize that China and India are becoming centres of global economic power that are increasingly challenging the global hegemony of the United States. The article ends with a conclusion on the contribution of the article and in particular points to the value of Bhabha’s notion of the in-between’ spaces as a way forward for understanding developments in the global business environment.